Exploring health systems readiness for domestic violence in Brazil and Palestine. (30th September 2020) - Colombini, M; d'Oliveira, A F; Alkhayyat, A; Shaheen, A; Garcia-Moreno, C; Feder, G; Bacchus, L
Abstract: Background: Increasing attention has been paid on health systems readiness around domestic violence (DV), a global health issue leading to adverse health consequences. This article aims to present a comparative synthesis of the health system pre-conditions necessary to enable integration of services for domestic violence in Brazil and Palestine. Methods: A health systems readiness assessment was conducted to explore health systems gaps. Multiple, data sources were used, ranging from qualitative interviews with various stakeholders (e.g. providers, health managers and key informants); structured facility observations (8 clinics); policy document reviews. Results: Our findings highlight deficiencies in policy and practice that need to be addressed for an effective response. Common preparedness gaps include unclear governance and unsupportive leadership structure; challenges around service delivery such as limited staff protection and limited coordination; and untrained health workforce. Our results illustrate the importance of having clear guidance on roles and responsibilities for both health managers and clinicians. In Brazil, although there is a legal and regulatory system on domestic violence, its implementation has been patchy as health regulations are not well-defined. In both settings, the limited higher-level commitment and political will to reduce violence has affected implementation. Limited guidance, coupled with limited training and perceived lack of support in the facility environment, also impacted on providers' knowledge and confidence in responding to violence. Fear of family retaliation affected frontline providers' actions in both countries. Conclusions: Our innovative framework helped identify anticipated readiness gaps. It has shown the importance of nurturing the role and values of managers and engaging the leadership across every system to reframe challenges, and strengthening routine practices to encourage staff engagement in responding to DV. Key messages: Conducting a health systems readiness assessment before integrating a new service can anticipate preparedness gaps and inform adaptation that will enhance service uptake and effectiveness. Critical systems gaps to address before integrating domestic violence services in healthcare include staff and managers' values, leadership and organisational support to frontline providers.